A Rare Cause of Small Bowel Obstruction: A Case Report - Chen, Piaopiao; Hu, Qiang; Wu, Jinfeng; Sun, Yuanshui (Frontiers in Surgery, 2022)
Introduction: Small bowel obstruction is a common surgical emergency abdominal condition in clinical practice. Fecalith is one of the rare causative factors, especially phytobezoars. Case report: We report the case of a 66-year-old man admitted with “abdominal pain with vomiting for 1 day”. Enhanced CT of the abdomen suggested incomplete small bowel obstruction. The symptomatic treatment with fasting, fluid replacement, gastrointestinal decompression, and antibiotics after the patient was admitted to the hospital. After 2 days of treatment, the patient's abdominal pain was not significantly relieved, so a decision was made to perform laparoscopic examination surgery. During surgery, a columnar foreign body was found embedded in the lumen of the small intestine about 10 cm away from the ileocecal region. Combined with the patient's preoperative history of consuming a large number of persimmons, the primary diagnosis of fecalith small intestinal obstruction was considered. We performed an enterotomy to remove the foreign body, and the procedure was uneventful. On postoperative day 7, the patient was discharged successfully. Conclusion: When we encounter a patient with intestinal obstruction without a history of surgery in our clinical work, we should take a careful history, especially about the consumption of foods that can cause phytoliths. When a patient has consumed a large amount of food that can cause phytobezoars before the abdominal pain, diagnostically we should consider it as phytobezoars intestinal obstruction, which helps to reduce the incidence of misdiagnosis and allows the patient to receive treatment timely and effectively.